THE ROLE OF THE MASS MEDIA IN THE PREVENTION OF IDEOLOGICAL THREATS IN THE REPUBLIC OF UZBEKISTAN (Conference Zone, 2022)
The article highlights the role and place of media in learning and education of youth. Today, the media play an important role in all aspects of public life. Through them, first of all, people are aware of the changes taking place in the socio-political, economic, cultural, spiritual life of society, as well as in the world community, interstate relations. They perceive them and express their attitude. The article also analyzes the growing role of the media in the spiritual life of society